Potential blood biomarkers in COPD cachexia - Mokari Yamchi, Amin; Kheirouri, Sorayya; Mokari-Yamchi, Ziba (Progress in Nutrition, 2020)
Weight loss and muscle wasting occur in a quarter of patients with chronic obstructive pulmonary disease (COPD) and are associated with shorter survival and reduced quality of life. Effective intervention for cachexia requires early detection that may help in preventing further depletion. Elevated concentrations of inflammatory biomarkers are observed in COPD patients and have been associated with several complications such as weight loss. In this review, we have studied the circulating inflammatory mediators (tumor necrosis factor, interleukin-6 and c-reactive protein) and energy balance hormones (adiponectin, leptin, ghrelin) as potential biomarker in early detection and management of cachexia in COPD. This review did not find firm support for causal relationship between biomarkers and cachexia. Most studies divided individuals into cachectic and non-cachectic groups based on current body mass index (BMI) or fat free mass index (FFMI) regardless of previous status. Future large longitudinal studies with BMI/FFMI matching are required. Also, combination of inflammatory biomarkers and energy homeostasis hormones may represent valuable biomarkers in the early detection of COPD cachexia.